The comprehensive impact on human body induced by resolution of growth hormone excess. Issue 4 (April 2018) - Zhang, Zhaoyun; Li, Qin; He, Wenqiang; Qiu, Huijia; Ye, Hongying; Wang, Yongfei; Shen, Ming; He, Min; Yu, Yifei; Shou, Xuefei; Huang, Chuanxin; Yu, Huan; et al.
Abstract : Context: Chronic excess of growth hormone (GH) often leads to systemic complications. The reversibility of these complications after GH resolution is not fully understood. Objective: To investigate when and to what extent will the comorbidities be ameliorated. Design: We conducted a prospective study comprising 24 patients with acromegaly, who achieved remission after transsphenoidal surgery. The dynamic changes of endocrine, cardiovascular, respiratory, sleep, bone and morphology parameters were evaluated at enrollment and 1 week, 1 month, 3 months, 6 months and 12 months after surgery. Results: Random GH dropped by 98.4% at the first day postoperatively. IGF-I index dropped by 50% and 64% at 1 week and 1 month respectively and remained unchanged onwards. Glucose metabolism improved significantly at 1 week and stabilized at 1 month. Testosterone in male patients recovered to normal range since 1 month. Systolic blood pressures dropped markedly at 3 months while diastolic blood pressures fell mildly at later visits. Abnormal lung function showed no improvement. The decrease of bone formation and resorption markers occurred at 1 week and 3 months, respectively. At 1 month, the tongue area declined while the airway volume increased significantly, accompanied with improved obstructive sleep apnea syndrome. Extremities, lips and nasal ala became smaller since 1 week. Liver, kidney and spleen volumes declined by 6.4, 15.9, 9.2%, respectively at 1 month. The volumes of pancreas and adrenal showed no change. Conclusions: The rapid resolution of excessive GH led to the reversible changes of systemic comorbidities in a time-dependent and organ-specific manner.